SPIRITUAL PATH, SPIRITUAL REALITY - Al Bantaniy, Yusuf Abul Mahasin Tajul Khalwati al-Maqassariy, 1626-1699. ([S.l.])
1 online resource
Keywords: A prominent mystic and renowned anti-colonial warrior from Indonesia, Shaykh Yusuf of Macassar (1626-1699), was exiled to South Africa where he played a pioneering role in laying the foundations of Islam. Offering a rich translation of Shaykh Yusuf's Arabic writings, Spiritual Path, Spiritual Reality fills an important gap on the works devoted to the spiritual dimension in the Muslim intellectual archive. The introduction gives insight into his life and an understanding of how his mysticism was connected to his political engagement. Focusing on Islamic mysticism - known as fsm - the volume covers areas of spiritual discipline of the self, metaphysics and gnostic knowledge. The style is pedagogical with an instructive tone in keeping with the f path.